A cruciform phthalocyanine pentad-based NIR-II photothermal agent for highly efficient tumor ablation. Issue 35 (29th July 2019) - Pan, Houhe; Li, Shukun; Kan, Jing-lan; Gong, Lei; Lin, Chenxiang; Liu, Wenping; Qi, Dongdong; Wang, Kang; Yan, Xuehai; Jiang, Jianzhuang
Abstract : The first molecular material-based PTA for the NIR-II photothermal therapy with high PCE of 58.3% was reported. The Zn4 -H2 Pc/DP NPs reveal good biocompatibility and notable tumor ablation ability in 1064 nm. Abstract : Photothermal therapy in the second near-infrared window (NIR-II, 1000–1700 nm) exhibits a significant advantage over the first near-infrared window (NIR-I, 650–950 nm) in terms of both maximum permissible exposure (MPE) and penetration depth. However, the thus far reported NIR-II photothermal agents (PTAs) have been focused just on inorganic semiconducting and organic polymeric semiconducting nanoparticles. Herein a novel cruciform phthalocyanine pentad was designed, synthesized, and characterized for the first time. The water-soluble nanoparticles (Zn4 –H2 Pc/DP NPs) assembled from this single molecular material with the help of DSPE–PEG2000 –OCH3 exhibit characteristic absorption in the NIR-II region at 1064 nm with a large extinction coefficient of 52 L g −1 cm −1, high photothermal conversion efficiency of 58.3%, and intense photoacoustic signal. Moreover, both in vitro and in vivo studies reveal the good biocompatibility and notable tumor ablation ability of Zn4 –H2 Pc/DP NPs under 1064 nm laser irradiation. Theoretical density functional theory calculations interpret the two-dimensional compressional wave energy-dissipation pathway over the broad saddle curved framework of the cruciform conjugated phthalocyanine pentad, rationalizing the efficient photothermal properties of corresponding Zn4 –H2 Pc/DP NPs in the NIR-II window.